Psychometric properties of the Korean version of questionnaires on adherence to physical distancing and health beliefs about COVID-19 in the general population - Hong, Youjin; An, Hoyoung; Cho, Eulah; Ahmed, Oli; Ahn, Myung Hee; Yoo, Soyoung; Chung, Seockhoon (Frontiers in Psychiatry, 2023)
Introduction We aimed to explore the psychometric properties of the Korean version of the questionnaires on adherence to physical distancing, health beliefs about COVID-19, and perceived social norms. Additionally, we examined how the various sections interacted with each other and viral anxiety and depression, and ultimately affected the adherence to physical distancing. Methods We gathered participants’ information on age, sex, marital status, or responses to the questions on COVID-19 via e-survey. Participants’ responses to rating scales including questionnaires on adherence to physical distancing, health beliefs about COVID-19, and perceived social norms, Stress and Anxiety to Viral Epidemics-6 items (SAVE-6), and Health Questionnaire-9 (PHQ-9) were collected. Results All 400 general population participated. The confirmatory factor analysis revealed a good model fit for adherence to physical distancing (CFI = 1.000, TLI = 1.019, RMSEA = .000, and SRMR = .034) and health beliefs about COVID-19 (CFI = .993, TLI = .991, RMSEA = .030, and SRMR = .052). Structural equation models showed that the effects of health beliefs and viral anxiety and depression were mediated mostly by personal injunctive norms. Fit measures indicated a good fit. (Chi-square = 24.425, df = 7, p<0.001; CFI = 0.966; RMSEA = 0.079) Conclusion The Korean version of questionnaire on adherence to physical distancing and health beliefs with COVID-19 showed a good reliability and validity among the general population in Korea. In addition, the effects of health beliefs, along with viral anxiety and depression, were mainly mediated by personal injunctive norms.